Relationship between femoral anteversion and tibial torsion: CT evaluation of 38 unilateral developmental dysplasia of the hip patients. Issue 5 (September 2018) - Cho, Kyu-Jin; Park, Kyung-Soon; Shin, Young-Rok; Yang, Hong-Yeol; Yoon, Taek-Rim
Introduction: Patients with developmental dysplasia of the hip (DDH) present with a wide spectrum of deformities. Few studies have assessed the relationship between femoral anteversion (FA) and rotational profile. The aim of this study is to evaluate the influence of FA on the lower extremity rotational profile by comparing tibial torsion (TT) between the extremities on both sides in patients with unilateral DDH, using computed tomography (CT). Patients and methods: Thirty eight patients with unilateral developmental dysplasia of the hip, who underwent a preoperative rotational profile CT scan at our institution, were evaluated. 3D rotational profile CT was performed, and FA and TT of the extremities on both sides were measured. Results: On individual comparison of the rotational profile, mean FA of the affected extremity showed a significantly higher value ( p = 0.006). But, there was no significant difference in mean TT between the 2 extremities. On group analysis, the excessive FA group (group B) showed significantly higher values of tibial torsion and tibial torsion side-to-side difference compared to the normal FA group (group A) ( p = 0.000, p = 0.011, respectively). Conclusions: Our study suggests that patients with DDH can present with excessive FA. Therefore, while treating patients who show excessive FA, surgeons must consider the possibility of a higher rotational profile of the affected extremity, before performing surgical treatments for DDH.